Synthesis and properties of a novel high temperature pyridine‐containing phthalonitrile polymer. Issue 24 (20th September 2016) - Xi, Zhenjie; Chen, Xinggang; Yu, Xiaoyan; Ma, Yuanhui; Ji, Puguang; Naito, Kimiyoshi; Ding, Huili; Qu, Xiongwei; Zhang, Qingxin
ABSTRACT: A novel pyridine‐containing aromatic phthalonitrile monomer, 2, 6‐bis[4‐(3, 4‐dicyanophenoxy)benzoyl]pyridine (BCBP) was synthesized from the nitro displacement of 4‐nitrophthalonitrile by the phenoxide of 2, 6‐bis (4‐hydroxybenzoyl)pyridine (BHBP). 4‐(Aminophenoxy) phthalonitrile (APPH) was selected to promote the curing reaction, and the curing behavior has been investigated by differential scanning calorimetric (DSC), suggesting a wide processing window about 64 °C. Different curing additive concentrations resulted in polymers with different crosslinking degrees and subsequently influenced the performance of resins. The resulting BCBP polymer exhibited high glass transition temperatures exceeding 400 °C, outstanding thermo‐oxidative stability with weight retention of 95% at 530 °C, indicating a significant improvement in thermal properties endowed by pyridine units. Additionally, it also showed a lower overall water absorption after submersion in boiling water for 50 hours. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3819–3825 Abstract : A novel phthalonitrile resin containing a pyridine structure has been successfully prepared. The high‐crosslinked thermoset exhibited excellent thermal and mechanical properties as well as good processability. Outstanding water resistance has also demonstrated its potential application for moist environment.